Perceptions of Auditor Independence and Official Ethical Guidelines. - Firth, Michael (The Accounting Review, 1980)
ABSTRACT: The paper examines the role and importance of auditor independence as perceived by various interested parties in the United Kingdom. A questionnaire postulating 29 auditor-client relationships was sent to a sample of both the preparers of and the users of financial statements. They were asked whether they thought auditor independence might be impaired for each relationship and what impact they thought this might have on investment and lending decisions. The results showed that non-independence was perceived by the respondents to impair investment and lending decisions. It was also found that there were significant differences in the perceptions of auditor independence, and the importance thereof, between the responses of the preparers of financial statements and the responses of the users of financial statements. The results showed that while the views of accountants working in professional practices agreed quite closely with the ethical guidelines on auditor independence published by the British Institutes of Chartered Accountants, the users of financial statements were much more skeptical of auditor independence.